(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In article the portrait and landscape according to Baurzhan Momyshul’s novel «the Front of Kurland» is considered. The author analyzing еру portraits in еру work, gives comparison of external and internal similarity and psychological changes of character that presented in the novel on concrete fragments of the novel. In the above-mentioned novel of B. Momyshul it is for the first time that the person depicted in a wartime, and also features of an image of labor research are shown. In article the attention to the comparative side in a section of changes of character and a spirit which are described as the lower layer of the nature of character of the person is proved and paid. In addition the comment referring to domestic and foreign portraits and landscapes of scientists are given.